Reproductive and obstetric outcomes following frozen embryo transfer: letrozole combined with human menopausal gonadotropin versus hormone replacement cycle - Guan, Hui-Juan; Tang, Huai-Yun; Li, Hui; Zhao, Jia-Hui; Song, Jia; Tang, Li-Sha; Hao, Yan-Lan (Frontiers in Endocrinology, 2026)
BackgroundThis study aimed to compare reproductive and obstetric outcomes between frozen embryo transfer (FET) cycles using letrozole combined with human menopausal gonadotropin (HMG) for ovulation induction (OI) and hormone replacement therapy (HRT) for endometrial preparation.MethodsA retrospective cohort study was conducted on 1,880 FET cycles from 2016 to 2024. Cycles were stratified into the OI group (n = 902) and HRT group (n = 978) based on the endometrial preparation protocol. The primary outcome was live birth rate (LBR). Secondary outcomes included clinical pregnancy rate (CPR) and obstetric complications. Exploratory subgroup analyses were performed based on ovulatory status (normal ovulation vs. ovulation disorders) and age (<35 years vs. ≥35 years).ResultsAfter adjustment for confounders, no statistically significant difference was observed in the primary outcome of LBR between the OI and HRT groups (OR = 1.145, 95% CI: 0.932–1.407; P = 0.198). Similarly, there was no significant difference in the secondary outcome of CPR (OR = 1.149, 95% CI: 0.944–1.398; P = 0.167). Analysis of other secondary outcomes revealed that the OI protocol was associated with a lower risk of cesarean section (OR = 0.619, 95% CI: 0.432–0.887; P = 0.009) and gestational diabetes mellitus (GDM) (OR = 0.339, 95% CI: 0.117–0.981; P = 0.046). Exploratory subgroup analyses suggested potential variations: In women with ovulation disorders, OI was associated with a higher CPR (OR = 1.624, 95% CI: 1.081–2.440; P = 0.020) and a lower preterm birth rate (OR = 0.682, 95% CI: 0.408–0.562; P = 0.023). In women ≥35 years, OI was associated with a markedly lower risk of GDM (OR = 0.038, 95% CI: 0.002–0.707; P = 0.028) and a non-significant trend toward higher LBR (OR = 1.521, 95% CI: 0.967–2.393; P = 0.07). In women <35 years, the OI cycle was associated with a lower cesarean section rate (OR = 641, 95% CI: 0.426–0.996; P = 0.034).ConclusionsAdjusted analysis revealed comparable LBR between the OI and HRT protocols. The OI protocol was associated with a lower risk of cesarean section and GDM in the overall population, with exploratory subgroup analyses suggesting potential differential effects in specific patient groups. These findings warrant prospective validation.